ANALYSIS OF NITROGEN FERTILIZER NEEDS WITH LEAF COLOR CHART AND FARMER PARTICIPATION FOR RICE PLANT (Oryza Sativa L.): ANALISIS KEBUTUHAN PUPUK NITROGEN DENGAN BAGAN WARNA DAUN DAN PARTISIPASI PETANI UNTUK TANAMAN PADI SAWAH (Oryza Sativa L.) - Achdiyat; Narita Ayu Putri (Jurnal Penyuluhan Pertanian, 2022)
Farmers' participation in the analysis of nitrogen fertilizer needs with leaf color chart for Paddy (Oryza sativa L.) plants in Kec. Tambaksari Regency. Ciamis, to find out: the level of participation and factors related to farmer participation. This activity was carried out from April 22, 2019 to July 26, 2019. The variables studied in this study consisted of independent variables (farmer characteristics and the role of advisors) and the dependent variable (participation). Data was collected by filling out a questionnaire (questionnaire), interviews, and secondary data (from related institutions). The results of the analysis of farmer participation include the category of "medium" or 61.2%, and the category of "high" or 38.8%, there is no category "low", because the cultivation of lowland rice is the main commodity, farmers in fertilizing to see the color of the leaves have been carried out . Then based on the results of the analysis, the factors related to participation are age, extension activities, facilitators and communicators. Farmers 'participation in the analysis of nitrogen fertilizer needs with the Leaf Color Chart for lowland rice are: The majority of farmers' participation rates are included in the "medium" category, and factors related to participation are age, extension activities, facilitators, and communicators; Farmer participation needs to be increased in order to provide optimal benefits, success must be carried out by all parties to work together to achieve goals